A Review and Comparative Analysis of Information Targeted to the General Public on the Websites of Breast Screening Programs in Canada - Anne J. Kearney, Julie Polisena and Andra Morrison (Healthcare Policy, 2017)
Organized breast screening programs in Canada recommend that women, usually 50–74 years of age, are screened regularly with mammography to reduce their risk of breast cancer death. There is increasing evidence that estimates of mortality reduction are overestimated and harms under-reported. This article will report on a review of the websites of 12 breast screening programs in Canada. The primary goal is to determine what information is provided to enable women to make an informed decision about mammography and whether choice is emphasized. All publicly available English language information was extracted from the 12 websites by two independent reviewers, using a data extraction sheet. Information extracted included eligible age, screening interval and potential benefits and harms. This review is relevant to policy makers and breast screening program staff so they can determine what additional or alternative information is required on their websites to enable women to make informed decisions.
Keywords: breast cancer, mammography, screening, informed consent